1989
DOI: 10.1177/019262338901700304
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Hepatotoxic and Lethal Effects of CCl by Partial Hepatectomy

Abstract: CCI, is a hepatotoxic haloalkane, capable of producing hepatocellular fatty degenention and centrilobular necrosis. Previous reports indicate induction of liver regeneration after 3 6 4 8 hr of CCI, treatment, which is considered as a secondary effect. The present investigation was undertaken to evaluate the primary effects of CCI, on hepatic DNA synthesis and to correlate liver regeneration with CCI, toxicity. These studies were conducted in normal and actively regenerating livers using male Spngue-Dawley rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 35 publications
3
59
0
Order By: Relevance
“…In contrast, if the rats are exposed to the same dose of CCl 4, 7 days post-PH when cell division has tapered off, injury progresses rapidly, liver fails, and the rats die, signifying complete loss of protection. 12,13 CAST expression data obtained in the current study coincide very well with these survival versus death observations reported earlier. 11 These findings are consistent with the notion that CAST overexpression may be the underlying mechanism of resiliency of the dividing/newly divided hepatocytes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In contrast, if the rats are exposed to the same dose of CCl 4, 7 days post-PH when cell division has tapered off, injury progresses rapidly, liver fails, and the rats die, signifying complete loss of protection. 12,13 CAST expression data obtained in the current study coincide very well with these survival versus death observations reported earlier. 11 These findings are consistent with the notion that CAST overexpression may be the underlying mechanism of resiliency of the dividing/newly divided hepatocytes.…”
Section: Discussionsupporting
confidence: 91%
“…22,48 Partial hepatectomy, the second model of liver cell division studied in the current investigation, is known to protect the experimental animals from hepatotoxicity. [11][12][13] However, the time of exposure of PH animals to the toxic insult is pivotal in determining whether the final outcome is favorable. 12,13 If the PH rats are exposed to model hepatotoxicant CCl 4 at the time of peak liver regeneration (from 2 to 4 days after PH), progression of injury is substantially lower, leading to recovery from liver injury and animal survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The liver also plays an important role in drug elimination and detoxification and liver damage may be caused by many xenobiotics, such as alcohol and many medicines, malnutrition, infection, and anaemia [24,25]. Liver damage is a widespread disease which, in most cases, involves oxidative stress and is characterized by a progressive evolution from steatosis to chronic hepatitis, fibrosis, cirrhosis and hepatocellular carcinoma [26].…”
Section: Liver and Biomarkers Of Hepatoxicitymentioning
confidence: 99%